2015
DOI: 10.1097/brs.0000000000000861
|View full text |Cite
|
Sign up to set email alerts
|

Selective Thoracic Fusion of Lenke I and II Curves Affects Sagittal Profiles But Not Sagittal or Spinopelvic Alignment

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 22 publications
5
26
4
Order By: Relevance
“…The radiographs were centered on T12 during inspiration, with a 2-meter distance between the lm and the focus. All images were transferred to a computer as digital images and evaluated using the image software Surgimap Spine (Nemaris Inc., New York, USA) [4,5,7,9].…”
Section: Study Design and Participantsmentioning
confidence: 99%
See 3 more Smart Citations
“…The radiographs were centered on T12 during inspiration, with a 2-meter distance between the lm and the focus. All images were transferred to a computer as digital images and evaluated using the image software Surgimap Spine (Nemaris Inc., New York, USA) [4,5,7,9].…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…During the surgical correction of adolescent scoliosis, direct vertebral rotation (DVR) in combination with rod derotation after pedicle screw instrumentation enables correction of rotational vertebral body deformity, achieving a su cient correction angle with a reduced fusion level while minimizing aggravated deformity and complications due to patient growth [7,8]. In the late 1990s, the literature showed use of the new method: DVR designed to foster rotational correction [3,4,[7][8][9]. The choice of an inappropriate fusion level may result in under-or overcorrection of major and compensatory curves, in turn potentially causing serious problems such as trunk imbalance and decompensation [10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes in sagittal parameters during the postoperative period can be expected in patients with both selective and non-selective fusion. Ries et al compared the group of 50 Lenke Type 1 and Type 2 patients with 32 healthy individuals and found that both the TK and LL were decreased after selective fusion in each group, whereas SVA and PT were not affected (12). As a result, they showed that, although the sagittal profile was altered; sagittal spinopelvic parameters did especially in the Lenke Type 1; however, sagittal spinopelvic parameters were similar in all Lenke types.…”
Section: A B C Dmentioning
confidence: 99%